Análise da diversidade genética e potencial biotecnológico da comunidade bacteriana associada a Coffea arabica L. de cultivo convencional e orgânico - Andrade, Paulo Henrique Marques de (Universidade Federal de São Carlos, 2019)
The present work had as objective the isolation, biochemical characterization, identification and analysis of the genetic diversity of the endophytic bacterial community associated with Coffea arabica L. culture from conventional and organic cultivation. The endophyte isolates were evaluated in vitro for the potential to promote direct plant growth (phosphate solubilization, biological nitrogen fixation and indole acetic acid production) and indirect (antagonism to phytopathogenic fungi) and enzymatic activity (amylolytic, cellulolytic, esterolytic, lipolytic, pectinolytic and proteolytic). Identification was performed by bacterial cell analysis by Matrix Assisted Laser Desorption / Ionization-Time-Of-Fligh (MALDI-TOF) of 59 endophytic isolates. Forty isolates were also identified by partial sequencing of the 16S rDNA gene for evaluation and comparing the diversity of endophytic bacterial communities associated with conventional and organic coffee. The analysis of diversity indicated that the endophytic bacterial community of coffee from the organic growing area is more diverse. A total of ten bacterial strains with potential for plant growth promotion were selected for in vivo inoculation in Coffea arabica L. seedlings and in vitro plant growth promotion indicators as well as macro and micronutrient content in leaf tissue were evaluated after 180 days of the first inoculation. Metagenomic analysis of the 16S rDNA gene was also performed on samples of rhizospheric soil from Coffea arabica L. from the same areas. From the analyzes it was possible to identify sequences of 1 phylum, 6 orders and 27 families among all the samples. Among them, the family Planctomycetaceae was the most abundant in the two areas analyzed, whereas the orders Xanthomonadales and Sphingomonadales were the ones that presented smaller relative abundance in the area ofconventional and organic cultivation, respectively. A total of 21 bacterial groups presented relative abundance with significant difference (p ≤ 0.05) between the rhizosphere samples of conventional and organic coffee, indicating the influence of the management on the bacterial diversity of the rhizospheric soil.
Analysis of genetic diversity and biotechnological potential of the bacterial community associated with Coffea arabica L. of conventional and organic cultivation
Keywords: Bactérias endofíticas; Solo rizosférico; Promoção de crescimento vegetal; Metagenômica; Coffea arabica L.; Endophytic bacteria; Rhizospheric soil; Plant growth promotion; Metagenomics; CIENCIAS AGRARIAS; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA